ANALISIS KOMPONEN KURIKULUM PELATIHAN GURU BAHASA INDONESIA DI MADRASAH BERBASIS KOMPETENSI - Ika Berdiati (Penamas, 2021)
The study aims to describe the results of analysis of the gap between the component of curriculum for Indonesia Language Training in Madrasahs with the needs for personal, pedagogical, professional and social competence of teachers and analysis of cource of training in the Indonesian Language Training curriculum in Madrasahs based on 21st century skills development needs for teachers. The research method is qualitative and quantitative using the quisioner instrument, interview instrument. The researcher as a key instrument. The results of the study concluded that there was still a gap between the curriculum components and the fulfilment of basic competencies. Personality and social competencies are not listed in the curriculum, while pedagogical and professional competencies are not only partially fulfilled. The adults learning strategies components are not in the document. Understanding knowledge of 21st century competency materials is very important and relevant to be taught in teacher traning through teacher traing institutions. However, it is not listed in the curriculum document